2014
DOI: 10.1039/c4ce00627e
|View full text |Cite
|
Sign up to set email alerts
|

Unusual upconversion emission from single NaYF4:Yb3+/Ho3+ microrods under NIR excitation

Abstract: Rare earth ion-doped upconversion materials show great potential applications in optical and optoelectronic devices due to their novel optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…Therefore, at least 4–5 up to over 10 intrinsic NaYF 4 phonons are required to bridge the 5 S 2 + 5 F 4 → 5 F 5 , 5 I 6 → 5 I 7 , and 5 I 7 → 5 I 8 nonradiative transitions, rendering such multiphonon relaxations not very probable. Nevertheless, numerous nearly resonant CR processes may participate in the population of the intermediate energy levels and enhance ETU 4 , which is required for the red 5 F 5 → 5 I 8 emission . Following relatively high values of the Judd–Offelt <4f 10 α[SL]J||U (2,4,6) ||4f 10 α′[S′L′]J′>| 2 parameters (which describe the theoretical probabilities of a transition between starting [SL]J and target [S′L′]J′ multiplets, see Table S2, Supporting Information), the 5 I 7 level could also be populated radiatively by 5 S 2 + 5 F 4 → 5 I 7 and 5 F 3 → 5 I 6,7 transitions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, at least 4–5 up to over 10 intrinsic NaYF 4 phonons are required to bridge the 5 S 2 + 5 F 4 → 5 F 5 , 5 I 6 → 5 I 7 , and 5 I 7 → 5 I 8 nonradiative transitions, rendering such multiphonon relaxations not very probable. Nevertheless, numerous nearly resonant CR processes may participate in the population of the intermediate energy levels and enhance ETU 4 , which is required for the red 5 F 5 → 5 I 8 emission . Following relatively high values of the Judd–Offelt <4f 10 α[SL]J||U (2,4,6) ||4f 10 α′[S′L′]J′>| 2 parameters (which describe the theoretical probabilities of a transition between starting [SL]J and target [S′L′]J′ multiplets, see Table S2, Supporting Information), the 5 I 7 level could also be populated radiatively by 5 S 2 + 5 F 4 → 5 I 7 and 5 F 3 → 5 I 6,7 transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand and solvent molecule vibrations (Figure ; stretching CO vibration: hν ≈ 1091 cm −1 , stretching COO vibration: hν ≈ 1640 cm −1 , bending CH 2  vibration: hν ≈ 1400 cm −1 , stretching CH 2  vibration: hν ≈ 2850 cm −1 , and OH vibration: hν ≈ 3400 cm −1 ) could also modulate the population of intermediate energy levels, thereby affecting the ETU efficiency Φ UC ( Figure ), the luminescence kinetics ( Figure and Figure S8, Supporting Information), P ‐dependent luminescence intensity (Figures S6 and S7, Supporting Information), as well as I G / I R ratio (Figure or Figure S5, Supporting Information), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, many UC fluoride materials (NaYF 4 , NaLuF 4 , LaF 3 , LiYF 4 and NaScF 4 ) have been successfully prepared by different methods, including hydrothermal method, solvothermal method, high-temperature thermal decomposition of trifluoroacate precursors and liquid-solid two-phase approaches [7][8][9][10][11]. Among them, NaYF 4 crystal has been considered as one of the most efficient host matrix for UC emission [12][13]. Recently, a new UC host matrix that the NaLuF 4 host matrix with same crystalline plane as NaYF 4 has been reported [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…6 Several research groups have devoted efforts to develop synthetic protocols for controlling the crystallization processes, aiming to obtain crystals with well-defined size distribution, shapes and specific spectroscopic properties. Gao et al 7 reported the synthesis of β-NaYF 4 :Yb 3+ /Ho 3+ crystals with controlled size and morphology using ethylenediaminetetraacetic acid as a chelator. There are a wide number of reports that describe syntheses of inorganic crystals via coprecipitation, solvo/hydrothermal, microwave and thermal decomposition routes.…”
Section: Introductionmentioning
confidence: 99%